Endocrine Emergencies in the Medical Intensive Care Unit. Issue 3 (July 2022) - Nasrullah, Adeel; Azharuddin, Syed; Young, Meilin; Kejas, Alexis; Dumont, Tiffany
Abstract : Endocrine emergencies are underdiagnosed and often overlooked amid the management of severe multisystem pathologies in critically ill patients in the medical intensive care unit (ICU). In an appropriate clinical scenario, a low threshold of suspicion should be kept to investigate for various life-threatening, yet completely treatable, endocrinopathies. Prompt identification and treatment of endocrine emergencies such as diabetic ketoacidosis, myxedema coma, thyroid storm, and/or adrenal insufficiency leads to fewer complications, shorter ICU and hospital stay, and improved survival. This review article entails common endocrine emergencies encountered in the ICU and addresses their epidemiology, pathophysiology, clinical presentation and management.